Markers of redox status in patients with nonalcoholic fatty liver disease - Erceg, Sanja; Tomašević, Ratko; Ninić, Ana; Pavlović, Aleksandar; Guzonjić, Azra; Vujčić, Sanja; Mamić, Milica; Mitrović, Bojan; Gluvić, Zoran; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, present in up to 30% of the adult population worldwide. Triglycerides accumulation in hepatocytes (steatosis) represents the root cause of NAFLD and is associated with oxidative stress, which could further lead to fibrosis and cell death of hepatocytes. The aim of this research was to identify redox status markers for predicting the risk of developing steatosis. 158 participants were included. Steatosis was confirmed by ultrasound in 101 subjects, while the remaining 57 were in the control group. The following markers of redox status were determined in serum and plasma samples of all subjects: superoxide dismutase 1 (SOD1), paraoxonase (PON1), malondialdehyde (MDA) and superoxide anion (O2.-). For this purpose, spectrophotometric methods and enzyme immunosorbent assays were used. SOD1 was statistically significantly higher (P